The Impact of Service Quality, Company Image and Switching Barrier on Customer Retention: Mediating Role of Customer Satisfaction - Maladi, Muhammad; Nirwanto, Nazief; Firdiansjah, Achmad (AIBPM Publisher, 2019)
A conceptual outline is offered that explore the consequences of service quality, company image, switching barriers on customer retention mediated by customer satisfaction at LB-LIA Banjarmasin. To test the framework, structural equation modelling technique is applied to data gathered from 141 students in this informal education institution. The results revealed that service quality has substantial effect on customer satisfaction and customer retention, corporate image has an effect on customer satisfaction while switching barriers do not significantly influence customer satisfaction or customer retention and lastly customer satisfaction has a major effect on customer retention. It is recommended that service quality, corporate image and customer satisfaction be maintained and switching barrier needs to be improved.